Systematic relationships in southern African Francolins as determined from mitochondrial DNA - Jakutowicz, Mariola Barbara (Division of Chemical Pathology, 2017)
The Francolins constitute the largest genus in the Galliform family Phasianidae. There is little accord concerning the taxonomic classification of its members. In the past, information on this group has been provided by morphological and palaeontological evidence. An investigation into the molecular history of this group is presented, using mitochondrial DNA (mtDNA) as an evolutionary tool. A comparison of mtDNA restriction fragment lengths has been used to help define the phylogenetic relationships between 13 southern African Francolin species and a selected outgroup, the Japanese Quail. Both cladistic and distance-based analytical methods have been used to construct phylogenies from the molecular fragment data. The trees relating the Francolins are in general agreement with the traditional classification based on morphological, behavioural and morphometric studies, but differ in the branching order of two species, F. levaillantii and F. hartlaubi. A recent proposal for the partitioning of the genus into two monophyletic assemblages of quail-like "partridges" and pheasant-like "francolins" is supported by mtDNA fragment data, with the exception of the two aberrant taxa. On the basis of the initial fragment size comparison, F. hartlaubi and F. levaillantii constitute part of an unresolved quadrichotomy at the base of the tree. A restriction endonuclease site mapping approach has been utilized to provide a deeper resolution for the molecular phylogeny. Detailed mtDNA restriction endonuclease maps of F. levaillantii, F. hartlaubi, two species representing the "partridge" and "francolin" monophyletic groups respectively, and also of the Madagascar Partridge, have been constructed. Phylogenetic analysis of this data has helped to resolve the problematic placement of the two aberrant taxa by showing an early separation of F. levaillantii from the "partridge" lineage, and of F. hartlaubi from the "francolin" lineage. The Madagascar Partridge was anticipated to be a likely sister-taxon to the whole group, but instead appears to have close relationships within the "partridge" lineage.